Trade-Off Between Enzymatic Antioxidant Defense and Accumulation of Organic Metabolite Affects Salt Tolerance of White Clover Associated with Redox, Water, and Metabolic Homeostases - Min Zhou; Yuting Wu; Yuchen Yang; Yan Yuan; Junnan Lin; Long Lin; Zhou Li (Plants)
White clover (Trifolium repens) is an excellent perennial cold-season ground-cover plant for municipal landscaping and urban greening. It is, therefore, widely distributed and utilized throughout the world. However, poor salt tolerance greatly limits its promotion and application. This study aims to investigate the difference in the mechanism of salt tolerance in relation to osmotic adjustment, enzymatic and nonenzymatic antioxidant defenses, and organic metabolites remodeling between salt-tolerant PI237292 (Trp004) and salt-sensitive Korla (KL). Results demonstrated that salt stress significantly induced chlorophyll loss, water imbalance, and accumulations of malondialdehyde (MDA), hydrogen peroxide (H2O2), and superoxide anion (O2.−), resulting in reduced cell membrane stability in two types of white clovers. However, Trp004 maintained significantly higher leaf relative water content and chlorophyll content as well as lower osmotic potential and oxidative damage, compared with KL under salt stress. Although Trp004 exhibited significantly lower activities of superoxide dismutase, peroxidase, catalase, ascorbate peroxidase, monodehydroasorbate reductase, dehydroascorbate reductase, and glutathione reductase than KL in response to salt stress, significantly higher ascorbic acid (ASA), dehydroascorbic acid (DHA), glutathione (GSH), glutathione disulfide (GSSG), ASA/DHA, and GSH/GSSG were detected in Trp004. These findings indicated a trade-off relationship between antioxidant enzymes and nonenzymatic antioxidants in different white clover genotypes adapting to salt stress. In addition, Trp004 accumulated more organic acids (glycolic acid, succinic acid, fumaric acid, malic acid, linolenic acid, and cis-sinapic acid), amino acids (serine, l-allothreonine, and 4-aminobutyric acid), sugars (tagatose, fructose, glucoheptose, cellobiose, and melezitose), and other metabolites (myo-inositol, arabitol, galactinol, cellobiotol, and stigmasterol) than KL when they suffered from the same salt concentration and duration of stress. These organic metabolites helped to maintain osmotic adjustment, energy supply, reactive oxygen species homeostasis, and cellular metabolic homeostasis with regard to salt stress. Trp004 can be used as a potential resource for cultivating in salinized soils.